CIRBP Ameliorates Neuronal Amyloid Toxicity via Antioxidative and Antiapoptotic Pathways in Primary Cortical Neurons. (27th February 2020) - Su, Fang; Yang, Shanshan; Wang, Hongcai; Qiao, Zhenkui; Zhao, Hong; Qu, Zhengyi
Abstract : It is generally accepted that the amyloid β (A β ) peptide toxicity contributes to neuronal loss and is involved in the initiation and progression of Alzheimer's disease (AD). Cold-inducible RNA-binding protein (CIRBP) is reported to be a general stress-response protein, which is induced by different stress conditions. Previous reports have shown the neuroprotective effects of CIRBP through the suppression of apoptosis via the Akt and ERK pathways. The objective of this study is to examine the effect of CIRBP against A β -induced toxicity in cultured rat primary cortical neurons and attempt to uncover its underlying mechanism. Here, MTT, LDH release, and TUNEL assays showed that CIRBP overexpression protected against both intracellular amyloid β - (iA β -) induced and A β 25-35 -induced cytotoxicity in rat primary cortical neurons. Electrophysiological changes responsible for iA β -induced neuronal toxicity, including an increase in neuronal resting membrane potentials and a decrease in K + currents, were reversed by CIRBP overexpression. Western blot results further showed that A β 25-35 treatment significantly increased the level of proapoptotic protein Bax, cleaved caspase-3, and cleaved caspase-9 and decreased the level of antiapoptotic factor Bcl-2, but were rescued by CIRBP overexpression. Furthermore, CIRBP overexpression prevented the elevation of ROS induced by A β 25-35 treatment by decreasing the activities of oxidative biomarker and increasing the activities of key enzymes in antioxidant system. Taken together, our findings suggested that CIRBP exerted protective effects against neuronal amyloid toxicity via antioxidative and antiapoptotic pathways, which may provide a promising candidate for amyloid-based AD prevention or therapy.